Dampak Positif dan Negatif Kemajuan Teknologi Digital - Muhammad Hafidl Zidan; Sausan Nabilah; Faqih Ash’Haabal Syai’Awwala; Zahra Davina Putri; Lintangsari Arum Siwi; Diva Febrianti Putri; Maulita Dwi Nispriliani; Vito Irsandya Arvin; Arif Widagdo (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study critically examines the dualistic paradigm of digital technology advancement across social humanities and educational landscapes through a critical literature review methodology. Synthesizing insights from network society and media convergence theories, the analysis delineates how digital infrastructure drives pedagogical innovation and household economic transformations while simultaneously inducing severe psychosocial pathologies. The systematic integration of multimedia instruments and electronic commerce platforms enhances efficiency, but unmonitored immersion triggers localized counterproductive behaviors such as cyberloafing and severe mental health distress including the fear of missing out. These findings underscore a critical tension between operational productivity and psychological degradation within contemporary digital environments, particularly among younger generations. Ultimately, mitigating these systemic vulnerabilities requires structured digital literacy regulations deployed cooperatively across institutional school frameworks and domestic family spheres to safeguard individual psychological resilience against algorithmic exploitation.